Answer:
![f(3)=7](https://img.qammunity.org/2020/formulas/mathematics/middle-school/5zcknt3kkv5a37wnvnm3e325spumswv0wn.png)
Explanation:
Given:
![f(x)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/g5as8f90m6mrh9dvzpro2yb3z0msz95zff.png)
0 -2
2 4
6 16
Let us first determine whether the rate of change of the function is constant or not.
The rate of change of the function is given as:
![m=(f(x_2)-f(x_1))/(x_2-x_1)](https://img.qammunity.org/2020/formulas/mathematics/high-school/gsz1veqfdjzfq5xze0aein5ush5p7o0mgo.png)
So, for
![x_1=0,f(0)=-2,x_2=2,f(2)=4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ep3du0truz4al7ms2olgdsojo4bwm2ydr1.png)
![m=(4-(-2))/(2-0)=(4+2)/(2)=(6)/(2)=3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/inozx2kygbexmqwsffawba7ngo0novo9iv.png)
For the next set of numbers,
![x_2 = 2, f(2)=4,x_3=6,f(6)=16](https://img.qammunity.org/2020/formulas/mathematics/middle-school/vkdux98t0cl12d8vblq33f1iz4tmntidgz.png)
![m=(16-4)/(6-2)=(12)/(4)=3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/l8gbxlln1tuahh0o0nj2dar6lbhinphcf4.png)
Therefore, the rate of change of the function is a constant. Therefore, the relationship is a linear relationship.
A linear relationship with a given point
and constant rate of change
is given as:
![y-y_1=m(x-x_1)\\y-(-2)=3(x-0)\\y+2=3x\\y=3x-2\\\therefore f(x)=3x-2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/4ys058k2leazc6m5x9ljonwxs5i149alin.png)
Now, value of
is obtained by plugging in 3 for
in the above expression.
![f(3)=3(3)-2\\f(3)=9-2=7](https://img.qammunity.org/2020/formulas/mathematics/middle-school/uyvuk63wg0akg4taq8212j9pajx6xmtq8r.png)